2019
DOI: 10.1177/0021998319886043
|View full text |Cite
|
Sign up to set email alerts
|

Recent developments in the processing of waste carbon fibre for thermoplastic composites – A review

Abstract: The aim of this paper is to highlight recent developments in the processing of waste carbon fibre for thermoplastic composites. Initially, injection moulding and nonwoven technologies have been used to integrate waste carbon fibres into fibre-reinforced thermoplastic composites. Recently, tape and hybrid yarn spinning technologies have been developed to produce tape and hybrid yarn structures from waste carbon fibre, which are then used to manufacture recycled carbon fibre-reinforced thermoplastics with much h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 60 publications
0
56
0
Order By: Relevance
“…They stated that the developed composites could be used in automotive interior parts, furniture, interior construction, sports, and leisure equipment. Khurshid et al [ 24 ] reported processing techniques to recycle waste carbon fiber for thermoset composite production. The waste carbon fiber generated during yarn and fabric manufacturing can be easily converted into wet‐laid and dry‐laid nonwovens.…”
Section: Introductionmentioning
confidence: 99%
“…They stated that the developed composites could be used in automotive interior parts, furniture, interior construction, sports, and leisure equipment. Khurshid et al [ 24 ] reported processing techniques to recycle waste carbon fiber for thermoset composite production. The waste carbon fiber generated during yarn and fabric manufacturing can be easily converted into wet‐laid and dry‐laid nonwovens.…”
Section: Introductionmentioning
confidence: 99%
“…CFRTP will achieve a wide potential if both polymer and CF manufacturers [146] continue to observe new applications and develop creative and low-cost technologies. The major CFRTP consumption sectors include the aerospace, defense, automotive, renewable energies, sports equipment, and construction industries [147]. For instance, aircraft makers have also been focusing on reducing the overall weight of aircraft so as to increase the efficiency of the product.…”
Section: Future Prospectsmentioning
confidence: 99%
“…This review article seeks to explain the state of the art in recycled carbon fiber textile manufacturing and subsequent processing into high-value automotive grade composites. Unlike other recent reviews that focus primarily on composites made of recycled fibers processed using yarn spinning [7] and fibers recycled using only pyrolysis [8], this review is indifferent towards any specific textile manufacturing and fiber recycling processes. First, recycling concepts, methods, and the expected properties are introduced.…”
Section: Introductionmentioning
confidence: 99%